(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
This paper addresses the implications of employing information and biological technologies in execution of medical and ultra-medical interventions, aimed at human enhancement. Reconsidering these principles especially those of equality and dignity supported by the conceptual framework of the medical act and the ethical norms that govern it, leads to the conclusion that no wealthy individual should be allowed to achieve, unlike others, the enhancement of the psychophysical abilities of Homo sapiens. Rather, the best biotechnologies should help sick or disabled individuals to recover their health, restoring their dignity and allowing them to participate fully in social relations.